The Influence of Banking Risk on Share Price and the Moderating Role of Inflation Rate - Melliza, Meliza (UI Scholars Hub, 2021)
This research examines the relationship between banking risk and the share price of governmentbanks in Indonesia. This research also discusses the moderating role of inflation towards banking risk and share price. This research employs the multiple regression analysis using the fixed-effect model to estimate the influence of banking risk on the share price and the role of inflation as a moderator variable. The findings reveal that both government and private banks’ liquidity risk positively and significantly influences the share price. Private banks’ credit risk has a positive and significant relationship with share price, while government banks’ credit risk has no significant effect on the share price. Inflation moderates the relationship between government banks’ liquidity risk and share price, but it fails to moderate the relationship between credit risk and share price. This research’s findings not only become guidance for government banks in maintaining their risks but also can be a reference for banking authority in setting banking policy.